An empirical analysis of consumers' concerns about privacy through using the internet - Teppei Koguchi; Toshifumi Kuroda; Takanori Ida (International Telecommunications Society (ITS), 2015)
In this research, an empirical analysis based on a questionnaire survey was carried out on these sorts of factors on the user side, and the effects that individual attributes and usage conditions have on concerns about privacy and on awareness and understanding of privacy policies were clarified. In this research, specifically we attempt to analyze the kinds of effects that "individual attributes and service-usage characteristics" have on "concerns about individual privacy and the understanding of privacy policies." Therefore, we established a model with the former as the dependent variables and the latter as the explanatory variables and carried out the estimates. For the estimates, we used data from a Web questionnaire survey with a sample size of about 2,000, and used a binary logit model and ordered logit model to identify the factors that affect concerns about individual privacy and understanding of privacy policies.
Keywords: 330